The Implementation of Incarnational Mission Among The Bugis Using Cultural Approach - Kanna, Armin Sukri (Jurnal Jaffray, 2014)
Culture as a medium to develop the cultural and ethnic identity of the Bugis wasmostly denied at the early encounter of Christianity with the indigenous people inSouth Sulawesi. The people who were baptized had been given a new identity to identifytheir Christianity. But on the other hand, it brought them out from their own culturalidentity that had shaped them. In several areas, Western elements influenced them verystrongly, like the dress code, name, and some customary practices in society.The history of Christian mission covers a long period and cannot be separatedfrom the situation that prevailed in it, which can be analyzed through observing thepractices, habits, and concerns of a representative sample of Christians. The diversityand coherence that appeared in every century from the first to the twenty-first of thehistory of Christianity should not be an obstacle in interaction between Christianityand the context. But it will be a media for observing and evaluating the totality ofChristian mission in communicating the Gospel. During this process one can see howthe gospel [Christ] is translated into the local forms and has been absorbed by thebelievers as well as transforming and discipline the believers themselves.The Bugis Christians, in relation with these cultural-religious forms, will beable to bear witness to Christ and present him in the midst of religions and cultures.Thus, Christ can be revealed in every religion and culture as the only Savior – usingthe form and the meaning – but he is not the monopoly of Christians. This emphasizesthe uniqueness and universality of Jesus Christ that God sent his only son to redeemand save human beings who believe in him from all religions and cultures (cf. John 3:16).